2008
DOI: 10.1136/emj.2007.052142
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgeon-performed ultrasound on diagnosis of abdominal pain

Abstract: Background:A randomised study was performed to evaluate the diagnostic accuracy of surgeon-performed ultrasound in the emergency department for patients presenting with abdominal pain.Methods:Surgeons responsible for the examination of study patients underwent 4 weeks of ultrasound training. 800 patients who were attending the emergency department for abdominal pain were randomised to undergo or not undergo surgeon-performed ultrasound as a complement to standard examination. The preliminary diagnosis made by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 27 publications
1
39
0
3
Order By: Relevance
“…Thus, we found that in biliary emergencies/ other syndromes, 34.51% versus 25% of patients were referred to surgery after US, which is in agreement with the literature data on emergency exploratory surgery for abdominal pain (24.1%) [17].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we found that in biliary emergencies/ other syndromes, 34.51% versus 25% of patients were referred to surgery after US, which is in agreement with the literature data on emergency exploratory surgery for abdominal pain (24.1%) [17].…”
Section: Discussionsupporting
confidence: 91%
“…The diagnosis based on clinical assessment and ultrasound corresponds with the final diagnosis in 53 - 83% of patients ((EL A2) [2,19,20,21]). In 70% of patients, an urgent diagnosis was correctly identified based on clinical assessment and ultrasound ((EL A2) [2]).…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier report we have shown an increase in diagnostic accuracy from 56.8% to 64.7% by the use of surgeon-performed ultrasound in the ED when patients present with abdominal pain 13. However, the benefits in further management have not been evaluated using a randomised controlled trial design.…”
mentioning
confidence: 96%
“…There are studies evaluating the role of surgeon-performed ultrasound in relation to diagnostic accuracy, validity and other potential benefits in abdominal pain management 7 13 – 16. In an earlier report we have shown an increase in diagnostic accuracy from 56.8% to 64.7% by the use of surgeon-performed ultrasound in the ED when patients present with abdominal pain 13.…”
mentioning
confidence: 99%